The Teachers’ Challenges of Teaching Speaking For Young Learners: A Case Study At English First (EF) - Herlinda Surya Kartika Putri; Nunung Nurjati (Departement of Mathematics Education, 2023)
This research aims to describe the challenges in teaching speaking for young leraners faced by English teachers and how the teachers solve the challenges in teaching speaking for young learners at English first (EF). The method used in this research was qualitative. The technique used to collect data in this research was interview with theree teachers at English First (EF). To analyze the data, the researcher used descriptive analysis techniques. The result showed that teaching speaking for young learners have several five challenges indications from Nunan (2010) that teachers face in the class, such as : 1) cognitive development, 2) motivation, 3) attention, 4) multi-level group, and 5) assessment. Most of challenges faced by teachers were 1) lack of students self-confidence, 2) unclear students’ pronunciation, and 3) parents involvement. The solution of the challenges faced by teachers in teaching speaking for young learners were different. The researcher found the solution that usually used by teachers were 1) grouping active students with students who were not active or lacked confidence, 2) using body gestures or Total Physical Response (TPR) method, and 3) the parents supposed to support to their children in learning English. It could be concluded that teachers face many challenges when teaching young learners to speak, but the teachers could overcome the challenges use the right solutions to overcome challenges and by creating fun, active, and creative learning.